An accurate model for predicting high frequency noise of nanoscale NMOS SOI transistors. (May 2017) - Shen, Yanfei; Cui, Jie; Mohammadi, Saeed
Highlights: A new combined HF short channel noise model that uses only one fitting parameter. A HF NMOS model for a commercial 45 nm CMOS SOI technology. Model validation by a practical RF low noise amplifier. Abstract: A nonlinear and scalable model suitable for predicting high frequency noise of N-type Metal Oxide Semiconductor (NMOS) transistors is presented. The model is developed for a commercial 45 nm CMOS SOI technology and its accuracy is validated through comparison with measured performance of a microwave low noise amplifier. The model employs the virtual source nonlinear core and adds parasitic elements to accurately simulate the RF behavior of multi-finger NMOS transistors up to 40 GHz. For the first time, the traditional long-channel thermal noise model is supplemented with an injection noise model to accurately represent the noise behavior of these short-channel transistors up to 26 GHz. The developed model is simple and easy to extract, yet very accurate.